The Role of Dialogical Patrol of the Turjawali Unit of the Samapta Unit in Preventing the Crime of Theft in the Jurisdiction of the Nganjuk Police - Prasetiyo, Tri Agung (Indonesian Journal of Police Studies, 2024)
This research was motivated by an increase in cases of curanmor crimes in the Nganjuk Police Jurisdiction from 2022 to 2023 in August. With preventive efforts, the role of dialogical patrols of the turjawali unit of the Nganjuk Police Samapta Unit in an effort to reduce curanmor crimes. The purpose of this study explains the role of dialogical patrols of the turjawali unit of the samapta unit in the prevention of curanmor criminal cases. Researchers use management theory, competency theory, POP (Problem-Oriented Policing) theory, cooperation theory, and communication theory. The concepts used are the role concept, patrol concept, dialogical patrol concept samapta, and the concept of motor vehicle theft. The police operational guidelines used in this study are Perkabaharkam Polri Number 1 of 2017 concerning patrols. This research uses a qualitative approach with the type of field research research, data collection techniques through observation, interviews, and document studies. The results of the study that the researchers found were discrepancies in the implementation of dialogical patrols of the turjawali unit with police operational guidelines, the patrol planning carried out was not specific, the ability of patrol members who had never attended vocational education, and the inaccuracy of selecting targets for the implementation of dialogical patrols of the turjawali unit. Researchers concluded that the implementation and role of dialogical patrols of the turjawali unit of the samapta unit in the prevention of curanmor crime was still not carried out properly. The researcher suggested that the Nganjuk Police Samapta Unit be more active in assisting relevant members in the implementation of dialogical patrols in accordance with operational guidelines for the operation, and the implementation of analysis and evaluation must be balanced with the proper anatomy of curanmor cases, as well as improving the ability of personnel through related training to support patrol activities.